Fermentasi Nira Nipah Dengan Variasi Kekentalan Untuk Produksi Bioetanol Menggunakan Teknik Amobilisasi Sel - Oci Khairani; Syaiful Bahri; Chairul Chairul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Ethanol consumption of the world for a variety of uses has increased very significantly in recent years. Therefore it is necessary to alternate sources of raw materials to manufacture bioethanol and bioethanol production can be increased. Nipa sap is one of potential materials to be processed into bioethanol. Availability of nypa palm land in Indonesia and a fairly high sugar content (15-20%) makes nipa sap has the potential to be processed into bioethanol. Through the process of fermentation using immobilized yeast which Sacharomyces cereviceae, glucose is converted into ethanol and carbon dioxide. Immobilization in the field of biotechnology is defined as a method used to put in physics or chemistry of a cell into a buffer in the form of solid materials, matrix, or membrane. Fermentation takes place in batches with a volume of 2 liters of fermentation medium, heavy beads 40 grams, initial pH of 5,0. Viscosity variation with the palm sap evaporation of 15%, 20%, 25% and fermentation time 24, 36, 48, 60, 72, 84 and 96 hours. The stirring speed of 200 rpm and temperature of fermentation at room temperature (25 – 30oC). Ethanol concentration was analyzed using Gas Chromatography. The maximum fermentation process is shown in viscosity with 25% evaporation and fermentation time 84 hours with the initial sugar concentration 221,163 mg/ml. Bioethanol concentration obtained under these conditions was 8,010% (v/v) or 63,223 mg/ml.Keywords : Bioethanol, Fermentation, Immobilized, Nipa Sap, Sacharomyces cereviceae